2013
DOI: 10.1039/c3ra22989k
|View full text |Cite
|
Sign up to set email alerts
|

Controlled fabrication of Si nanoparticles on graphene sheets for Li-ion batteries

Abstract: A new route is presented for the synthesis of Si nanoparticle/Graphene (Si-Gr) composite by a sonochemical method and then magnesiothermic reduction process. During the process, silica particles were firstly synthesized and deposited on the surface of graphene oxide (SiO2-GO) by ultrasonic waves, subsequent lowtemperature magnesiothermic reduction transformed SiO 2 to Si nanoparticles in situ on graphene sheets. The phase of the obtained materials was influenced by the weight ratio of Mg to SiO 2-GO. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…When the capacity is restricted to 500 mAh/g, these composites operate reliably up to 90 cycles. 155,156 More complex nano Si architectures using carbon nanotubes, 157 graphene, 158,159 and other carbon or oxide supports 7,160,161 have also been developed and shown excellent capacity retention, but these have been synthesized only on the laboratory scale and further scale-up could be costly. In addition, the low areal loading along with the nano Si architectures results in low-volumetric energy density.…”
Section: High-voltage Cathode Materialsmentioning
confidence: 99%
“…When the capacity is restricted to 500 mAh/g, these composites operate reliably up to 90 cycles. 155,156 More complex nano Si architectures using carbon nanotubes, 157 graphene, 158,159 and other carbon or oxide supports 7,160,161 have also been developed and shown excellent capacity retention, but these have been synthesized only on the laboratory scale and further scale-up could be costly. In addition, the low areal loading along with the nano Si architectures results in low-volumetric energy density.…”
Section: High-voltage Cathode Materialsmentioning
confidence: 99%
“…We adopted graphene oxide (GO) in this study because it has shown great potential in the development of energy storage devices8,10,11,[30][31][32][33][34] and other applications7,9,35 . When GO suspension was mixed with the solution of PANi and poly (2-acrylamido-2methyl-1-propanesulfonic acid) (denoted PAMPA)groups of GO and the positively charged nitrogen atoms of both PANi and PAMPA (Figure S1acontains the polymers' morphology); leaving the mixture at 95 °C for 12 h changed the colour from brown to black.…”
mentioning
confidence: 99%
“…The G-band is characteristic of graphitic sheets, corresponding to a well defined sp 2 carbon-type structure, whereas the D-band can be attributed to the presence of defects within the hexagonal graphitic structure. The intensity ratio of ID/IG is a parameter to evaluate the graphitization degree of the carbonaceous materials and the density of defects in graphene-based materials [35,36]. It can be seen that, after the thermal treatment, the ID/IG ratio decreases from 0.97 of the RGO film to 0.89 of the RGO/Si film, which can be attributed to a significant increase of the in-plane sp 2 domain size.…”
Section: Resultsmentioning
confidence: 92%